K/Ka ultra wide band amplifier design - Asim Ali. (2008)
In this report the design and performance of amplifier in K/Ka band range are presented. The results of simulations are discussed. A broadband hybrid MIC amplifier operating from 18 to 30GHz is developed for K through Ka-band applications using NEC FET chip (NE24200) and Rogers Duriod substrate having dielectric constant of Er=2.2 and thickness of 30 mil. Amplifier design and its performance simulations were conducted using Agilent, Advance Design System one of the best microwave circuit design software available in the market. Hybrid MIC technology was adopted because of its low cost, flexibility of tuning during production cycle and more over this design can also be served as prototype before the mass production in the form of MMIC.